An Experimental Study on Concrete’s Durability and Mechanical Characteristics Subjected to Different Curing Regimes - Edgar L. S. Borrero; Visar Farhangi; Kazem Jadidi; Moses Karakouzian (Civil Engineering Journal, 2021)
Considering a constant demand in construction of concrete structures to develop novel approaches for predicting the concert’s properties, a host of investigations were performed on concrete’s mechanical properties and durability under various curing regimes. However, few studies were concerned with evaluating the concrete’s durability using non-destructive concrete surface resistivity tests by applying various curing conditions. The present study compares the influence of different curing regimes on durability and compressive strength of concrete to recommend the most effective curing conditions on concrete’s characteristics.  Five curing conditions including ambient, laboratory, dry oven, wet oven and 7-days were analyzed. Accordingly, a non-destructive concrete surface resistivity test was performed on the concrete specimens using hand-held Wenner Resipod probe meter as a reliable and rapid approach. To analyze specimen’s durability, results of the surface sensitivity tests were correlated to chloride ion penetration rate based on the cylinder specimen dimensions and the degree of chloride ion penetration. The compressive strength tests were conducted on the specimens after 7, 28 and 56 days to determine the effect of curing conditions at different ages. Based on the reported outcomes, applying the wet oven curing regime results in higher compressive strength and durability compared to the other curing conditions. Doi: 10.28991/cej-2021-03091681 Full Text: PDF